A spatial-focal error concealment scheme for corrupted focal stack video - Wu, Kejun (2023)
Focal stack image sequences can be regarded as successive frames of videos, which are densely captured by focusing on a stack of focal planes. This type of data is able to provide focus cues for display technologies. Before the displays on the user side, focal stack video is possibly corrupted during compression, storage and transmission chains, generating error frames on the decoder side. The error regions are difficult to be recovered due to the focal changes among frames. Conventional error concealment methods result in sharpness inconsistency between recovered regions and their spatial adjacent regions. Motivated by this, in this paper, we propose a spatial-focal error concealment scheme specialized for focal stack videos. The spatial adjacent regions around an error region are employed to reveal the prediction relations between error frame and focal adjacent frames. Gaussian blur filtering and Lucy-Richardson deblur filtering are applied to simulate the video focal changes. In this way, the error regions can be well recovered by exploiting the spatial-focal information. Experiment results show that the proposed scheme can achieve the highest objective quality in terms of PSNR and SSIM. It can also obtain the best subjective quality with sharpness consistency in recovered regions and without block effect.